Asymptomatic rectal carriage of blaKPC producing carbapenem‐resistant Enterobacteriaceae: who is prone to become clinically infected?. (7th May 2012) - Schechner, V.; Kotlovsky, T.; Kazma, M.; Mishali, H.; Schwartz, D.; Navon‐Venezia, S.; Schwaber, M. J.; Carmeli, Y.
Abstract Carbapenem‐resistant Enterobacteriaceae (CRE) are emerging extremely drug‐resistant pathogens; blaKPC is the predominant carbapenemase in Israel. Early detection of asymptomatic rectal carriers is important for infection control purposes. We aimed to determine who among newly identified CRE rectal carriers is prone to have a subsequent clinical specimen with CRE. A matched case‐control study was conducted in a tertiary care teaching hospital in Israel. Cases with a primary positive CRE rectal test and subsequent CRE clinical specimens were matched in a 1:2 ratio with CRE rectal carriers who did not develop subsequent CRE clinical specimens (controls). Matching was based on calendar time of primary CRE isolation, whether the primary CRE isolation was ≤48 h or >48 h after hospital admission, and time at risk to have a subsequent clinical specimen. Data were extracted from the patients' medical records and from the hospital's computerized database. One hundred and thirty‐two newly identified CRE rectal carriers (44 cases, 88 controls) were included. The median time interval between screening and subsequent clinical specimens was 11 days (range, 3–27); 86% of the clinical specimens were classified as true infections. Independent predictors of subsequent CRE clinical specimens were: admission to the intensive care unit, having a central venous catheter, receipt of antibiotics, and diabetes mellitus. Identification of the risk factors for subsequent infections among CRE‐colonized patients can be used to control modifiable risk factors and to direct empirical antimicrobial therapy when necessary.